Bibliotecas escolares em cooperativas de ensino: relato de caso da Biblioteca da Escola Educativa na cidade de São Carlos- SP - De Campli, Graziella Fernanda (2021)
The research question about school libraries within the scope of the theoretical trajectory of consolidating the field of research in Information Science (CI) has been contextualized through the presentation of concepts and general definitions about the research developed in School Libraries. Thus, a basic research has been carried out based on a descriptive analysis of the context that represents the school libraries in private educational institutions in São Carlos, highlighting the situation of the library at Escola Educativa, for which an experience report of the functionalities of the school library in a teaching cooperative was drawn up. The objective was presenting general concepts and definitions that punctuate the understandings assumed in CI research in a School Library, identifying and describing census data in School Libraries in Brazil. It also aims presenting quantitative data in school libraries and private educational institutions in the city of São Carlos; describing the educational management model either in Cooperatives or at Escola Educativa, as well as analyzing the context of the constitution of school libraries in the city of São Carlos, in private institutions, highlighting the case Escola Ecucativa. The educational library at the Cooperativa de Ensino Educativa was participative and active in the formation of the student body, complying with the current legislation and being adequate to the proposed Educational Management model, where the benefit of this type of teaching cooperative is to be participatory.